Insecticide resistance in mosquitoes: Current status, mechanism, monitoring and innovative strategies for sustainable vector control - Divya Kataria; Sangeeta Janjoter; Nisha Dahiya; Mahima Yadav; Ritu Yadav; Vaishali Verma; Neelam Sehrawat (Molecular Biology Reports, 2026)

Seaweed under threat: Global perspectives on heavy metal exposure and public health implications - Mahima Ranjan Acharjee; Shariqul Islam; Hrishika Barua; Arafat Islam Shuvo; Mohammad Himel Mahamud (Food Control, 2026)

Assessment of Lobster Fisheries in Cox’s Bazar, Bangladesh: Fishing Technique, Species Composition and Value Chain Dynamics - Md Ariful Islam Milon; Naimur Rahman Naim; Mahima Ranjan Acharjee; Avijit Talukder (Thalassas: An International Journal of Marine Sciences, 2026)

Geochemical source apportionment, pollution indices, and Monte Carlo-based health risk assessment of trace elements in soil and surface water from the Mirsarai Export Processing Zone (MEPZ), Bangladesh - Md. Shazzadur Rahman; Md. Golam Mostafa; Mohammad Moniruzzaman; Mahima Ranjan Acharjee; Lutfa Ara Takeya; Md. Aminur Rahman; Abubakr M. Idris; Md. Ripaj Uddin (Regional Studies in Marine Science, 2026)

Preparation, characterization, and in-vivo evaluation of a polyherbal gel for anti-arthritic potential using medicinal plant extracts - Supriya Garg; Vaishali; Bhuwanendra Singh; Piyush Kumar Singhal; Arvind Kumar; Mahima (Next Research, 2026)

Integrated organic petrography, stable isotopes, and geochemistry of Rajmahal coals (India): Implications on depositional conditions - Mahima Panda; Ishwar Rahi; James C. Hower; Vivian A. Edwards; Anupam Sharma; Sk. Md. Equeenuddin; Sourav Ganguly; Bodhisatwa Hazra (International Journal of Coal Geology, 2026)

PFAS immobilization with soil amendments – How immobilized is immobilized? - Albert L. Juhasz; Tanya Cáceres; Ruby Jones; Farzana Kastury; Mahima Seeborun; Carina Herde; Michelle Cavallaro (Environmental Pollution, 2026)

Integrated computational and in vitro investigation to explore the preliminary anti-proliferative and anti-mitotic potential of γ-oryzanol against breast cancer - Mahima Sukhadia; Honey Patel; Adarsh Gupta; Rahul Jawarkar; Umang Shah; Alkeshkumar Patel; Keval Raval (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Pharmacognostical standardization and in-silico anticancer study of selected medicinal plants obtained polyherbal extract - Pratiksha Tyagi; Bhuwanendra Singh; Mahima; Piyush Kumar Singhal; Arvind Kumar; Vaishali (Next Research, 2026)

Automatic Detection of Motor Unit Fractions in Multiscanning EMG Recordings - Mahima Kallingal Muraleedharan; Cristina Mariscal; Javier Rodríguez-Falces; Javier Navallas; Armando Malanda (Annals of Biomedical Engineering, 2026)

Multistage triaxial behavior of gas hydrate-bearing soil across variable cementation coefficients - Mahima S. Rao; Ramesh Kannan Kandasami (Ocean Engineering, 2026)

Ethyl cellulose nanoparticles loaded with lyophilized Ocimum tenuiflorum: development and assessment for anti-bacterial and anti-cancer properties - Bintu Wadhwani; Mahima Chauhan; Mayora Varshney; Swati Dubey; Mohit Sanduja; Amit Kumar (Next Research, 2026)

Amelioration of artificial diets for Zeugodacus cucurbitae using marine and freshwater algal supplements - Mahima Ramkissoon; Sunita Facknath; Nadeem Nazurally (Journal of Asia-Pacific Entomology, 2026)

Graphene-directed zinc-MOF sulfidation for flexible solid-state supercapacitors with high practical energy density - Vít Kvasnička; Vishal Shrivastav; Shashank Sundriyal; Aby Cheruvathoor Poulose; Mansi; Vaishali Shrivastav; Wojciech Nogala; Mahima Khandelwal; Smita Talande; Radek Zbořil; Aristides Bakandritsos (Chemical Engineering Journal, 2026)

PRISMA Imaging Spectroscopy Reveals Topographic Control Over Canopy Nitrogen Variability in Subtropical Himalayan Forests - Mahima .; Hitendra Padalia; Taibanganba Watham; Ishwari Datt Rai; Subrata Nandy (Journal of the Indian Society of Remote Sensing, 2026)

Fungal cellulases: a comprehensive review on production, innovations, and applications - Mahima; Varsha Rani; Kunwar Vishal; Pawan Kumar Doharey; Aiman Tanveer; Pramod K. Yadav; Dinesh Yadav (Archives of Microbiology, 2026)

Quantitative compositional characterization of keropok lekor reformulated with seaweed and soy protein: Analytical validation of nutrient and fatty-acid profiles - Bappy Chowdhury; Md Ibnul Bakhtier Kaif; Jannatul Ferdausi Zaba; Payel Chowdhury; Mahima Ranjan Acharjee; K.M. Aminul Ehsan; Mst. Shahanaj Pervin; Naseha Salsabil Fabia; Nizaha Juhaida Mohamad (Food and Humanity, 2026)

Plant-enriched poultry products: A novel approach using functional ingredients in chicken meatballs - Md. Nehan Kabir; Syamun Naher; Mahima Ranjan Acharjee; Meherunnesa Chowdhury Sumy; Md. Manirul Islam (Food and Humanity, 2026)

From water and sediment to seafood: Heavy metal contamination and human health risk in wild and cultured oysters from a developing coastal region - Mahima Ranjan Acharjee; Subeda Newase; Sadia Afrin; Shariqul Islam; Md. Abdullah Al Mamun Hridoy; Mohammad Ekramul Haque; Trina Das; Sifatun Nur; Helena Khatoon; Tashrif Mahmud Minhaz; Yeasmin Nahar Jolly; Mohammed Shariful Azam; et al. (Marine Pollution Bulletin, 2026)

Barnacles as silent sentinels of microplastic pollution: Evidence from Gujarat coast, India and a global meta-analysis of sessile marine species - Mahima Doshi; Krupal Patel; Jigneshkumar Trivedi (Marine Pollution Bulletin, 2026)

Role of hydrate cementation habits on the geomechanical behavior of hydrate bearing sediments - Sahil Wani; Mahima S. Rao; Ramesh Kannan Kandasami (Engineering Geology, 2026)

Comparative Assessment of Toxic Heavy Metals Contamination in Farmed and Wild Fish in Bangladesh, and Implications for Human Health - Nahida Akter; Udoy Das; Mahima Ranjan Acharjee; Md. Mushfiqur Rahman; Arnob Ghosh; Helena Khatoon; Md. Hasan Faruque; Md. Habibullah-Al-Mamun (Biological Trace Element Research, 2026)

Comparative impacts of mono- and mixed microalgal diets on growth, survival, and nutritional composition of the edible oyster (Crassostrea belcheri) - Mahima Ranjan Acharjee; Subeda Newase; Mohammad Ekramul Haque; Trina Das; Sifatun Nur; Sadia Afrin; Zahidul Islam; S. M. Rashadul Islam; Tashrif Mahmud Minhaz; Helena Khatoon (Aquaculture International, 2026)

Cimicifugic acid B, a hydroxycinnamic acid ester of Cimicifuga sp., exhibits strong antiproliferative and cytotoxic potential against cervical cancer cells - Shireen Fatima; Mahima Verma; Uzma Shahab; Saheem Ahmad; Bodor Bin sheeha; Paridhi Puri; Safia Obaidur Rab; Omar W. Althomali; Irfan Ahmad Ansari (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Study on evaluation of effects of electromagnetic radiation on pollen viability in some commonly occurring plant species following different staining methods - Ankita Sharma; Neeru Bala; Mahima Sharma; Jatinder Kaur Katnoria; Shalini Bahel (Protoplasma, 2026)

Advanced machine learning models for accurate water quality classification and WQI prediction: Implications for aquatic disease risk management - Md. Abdullah Al Mamun Hridoy; Abdullah Ibna Shawkat; Chiara Bordin; Mahima Ranjan Acharjee; Andleeb Masood; Azeez Olalekan Baki; Md. Abdullah Al Mamun (Science of The Total Environment, 2025)

Emerging paradigms in diabetic neuropathy: Epigenetics, phytotherapy, machine-learning-based diagnostics and clinical trials of herbal interventions - Poonam Vashishta; Mahima Chauhan; Rajesh Asija (Next Research, 2025)

From pan to plate: How traditional cooking alters the nutritional composition, lipid integrity, and health-promoting indices of Rohu (Labeo rohita) - Anik Saha; Bappy Chowdhury; Srikanta Ghosh; ASM Nafis Sadekeen; Mahima Ranjan Acharjee; Narayan Datta; Omme Johora Tarin; Ahmedur Rahman; Mohammad Mozibul Haque; Monsur Ahmad (International Journal of Gastronomy and Food Science, 2025)

Constructed wetlands as a sustainable solution for pesticide pollution mitigation - Jyoti Singh; Mahima Choudhary; Rajesh Singh; Sujata Kashyap; Vinay Kumar Tyagi; Kalzang Chhoden; Sandeep Singh (Current Opinion in Environmental Science & Health, 2025)

Metagenomic analysis of viral diversity in Portuguese bats - Mahima Hemnani; Mustafa Karatas; Andreia V S Cruz; Priscilla Gomes da Silva; Gertrude Thompson; Patrícia Poeta; Hugo Rebelo; Jelle Matthijnssens; João R Mesquita (Veterinary Research Communications, 2025)
Bats are highly diverse mammals and known reservoirs of numerous zoonotic viruses. Their role in the ecology of emerging infectious diseases continues to be of significant interest. This study aimed to evaluate the occurrence of coronaviruses (CoVs) in Portuguese bats and predict the affinity of their spike proteins with the aminopeptidase N (APN) receptor of several host species. The study also explored the viral diversity in bat samples using metagenomic sequencing. Ten bats (five Myotis myotis and five Miniopterus schreibersii ) were captured at an underground roost in 2022 (Central Portugal), and fecal samples, oral, and anal swabs were collected ( n = 27). A Pan-CoV nested RT-PCR was used for initial screening, followed by viral metagenomic sequencing of all fecal samples and one CoV-positive buccal swab. In silico protein docking studies were performed between a Portuguese bat CoV spike protein and APNs of bats, pigs, and humans. Pan-CoV nested RT-PCR identified three positive samples: two fecal samples and one buccal sample. Metagenomic sequencing allowed us to determine two near complete CoV genomes. Protein docking predicted strong binding of this spike protein to bat, porcine, and human APN receptors. Metagenomics also identified picornaviruses, adenovirus, and dependoparvovirus in fecal samples. This study reports the first near complete genome sequences of two members of the Alphacoronavirus genus from a Portuguese bat The identification of other viral families highlights the diverse virome of these cave-dwelling bat species. Protein docking studies suggest a potential for cross-species transmission of this bat CoV between bats, porcines and humans, though further research is needed to confirm these interactions.

Molecular epidemiology and phylogenetic relationships of Theileria spp. in cattle from Marathwada region of Maharashtra state, India - Sachin S. Waghmare; Gajanan M. Chigure; Jagdish J. Gudewar; Satish S. Gaikwad; Nitin D. Jadhav; Pravin R. Rathod; Suresh G. Jadhao; M. F. M. F. Siddiqui; Meera P. Sakhare; Mahima R. Narawade; Anil Kumar Sharma (Tropical Animal Health and Production, 2025)

Mosquito-based transmission-blocking vaccine candidates for malaria: progress, challenges, and innovations - Nisha Dahiya; Mahima Yadav; Divya Kataria; Sangeeta Janjoter; Neelam Sehrawat (Molecular Biology Reports, 2025)

Novel therapeutic strategies targeting infections caused by P. aeruginosa biofilm - Rajeshwari Lekhwar; Sunil Kumar; Mahima Tripathi; Saurabh Gangola; Anil Kumar Sharma (Molecular Biology Reports, 2025)

Revolutionizing aquafeeds: Enhancing growth and immunity in Mystus gulio with Coccomyxa onubensis - Subeda Newase; Mahima Ranjan Acharjee; Mohammad Ekramul Haque; Sifatun Nur; Trina Das; Sadia Afrin; Razia Sultana; Helena Khatoon (Journal of Applied Phycology, 2025)

Molecular characterization and bioinformatic analysis of SGU protein in Anopheles culicifacies as target for transmission blocking activity - Hitesh Singh; Manisha Kirar; Mahima Yadav; Nisha Dahiya; Sangeeta Janjoter; Neelam Sehrawat (Immunologic Research, 2025)

Spatial assessment of groundwater contamination and associated health risk using pollution indices in Kathmandu Valley, Nepal - Manisha Ghimire; Naina Byanjankar; Mahima Joshi; Sayaboong Rai; Swastika Sapkota; Suman SK; Rachna Jha; Tista Prasai Joshi (Environmental Science and Pollution Research, 2025)

Uptake, Translocation, and Assimilation of Molybdenum and Chlorine in Plants, and their Regulatory Roles in Physiological Functions, Molecular Changes, and Genetic Expression - Mahima Misti Sarkar; Nirmali Gogoi (Journal of Plant Growth Regulation, 2025)

Croquemort-scavenger receptor class B 2 (scrbq2) gene in Anopheles stephensi: Molecular characterization and expression analysis after blood feeding - Nisha Dahiya; Mahima Yadav; Vartika Srivastava; Sangeeta Janjoter; Divya Kataria; Rajnikant Dixit; Neelam Sehrawat (Journal of Biosciences, 2025)

Effect of flow velocity and particle concentration on cotransport of zinc oxide and copper oxide nanoparticles in soil - Mahima John Horta; N. Seetha; L.K.S.V. Prasad Sallangi (Journal of Contaminant Hydrology, 2025)

Upconverting nano-paste in 3D-printed phone camera setup for soil phyto-iron sensing - T.S. Abhijith; Mahima Chandel; Neeraj Moun; Sarita Kataria; Kamaljit Kaur; Gunasekhar Nachimuthu; Mei-Yi Liao; VijayaKumar Shanmugam (Analytica Chimica Acta, 2025)

Tailoring plants as photosynthetic production chassis for small molecules - Connor Tansley; Mahima; Melissa Salmon; Daria Golubova; Honghao Su; Nicola Patron (Phytochemistry Letters, 2025)

Analysis of the shoreline dynamics and land use-land cover changes on Kutubdia Island, Bangladesh - Mahima Ranjan Acharjee; Subeda Newase; Hrishika Barua; Avijit Talukder (Journal of Coastal Conservation, 2025)

Ecofriendly agriculture pest control using pheromone packed programed nanovolcanoes framed by graphene oxide - Kamaljit Kaur; Mahima Chandel; Vinay Kumar Thirumalahatti Munikrishnappa; Prem Kumar; Bandana Kumari Sahu; Momin Ahamed; Sowmya Manjunath; Markandeya Gorantla; Shannon Olsson; Eswaramoorthy Muthusamy; Kesavan Subaharan; Vijayakumar Shanmugam (Clean Technologies and Environmental Policy, 2025)

Designing a multi-epitope vaccine against the midgut-specific fibrinogen-related protein 1(FREP1) of Anopheles stephensi to enhance protection against the malaria parasite: a step beyond traditional vaccine development approaches - Mahima Yadav; Nisha Dahiya; Hitesh Singh; Divya Kataria; Sangeeta Janjoter; Neelam Sehrawat (Biotechnology Letters, 2025)

An 18 base pair in-frame deletion in the degron tail of IAA2 provides resistance to 2,4-D and dicamba in Brassica tournefortii - Yuanlin Qi; Mahima Krishnan; Matthew Tucker; Peter Boutsalis; Christopher Preston (Pesticide Biochemistry and Physiology, 2025)

Molybdenum single-atom-bridged ReS2–graphene heterostructures for boosting supercapacitor performance - Mahima Khandelwal; Ievgen Obraztsov; Aby Cheruvathoor Poulose; Shashank Sundriyal; Gabor Ersek; Oleg Usoltsev; Laura Simonelli; Giuseppe Portale; Radek Zbořil; Aristides Bakandritsos (Chemical Engineering Journal, 2025)

Biotechnological advances in saffron: tissue culture challenges and future scope - Vishal Gupta; Mehak Gupta; Sushil Kumar Gupta; Shaily Javeria; Ayushi Sharma; Zakir Amin; Vinod Pandit; Mahima Sharma (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

3-Acetyl-11-keto-β-boswellic acid (AKBA) induced antiproliferative effect by suppressing Notch signaling pathway and synergistic interaction with cisplatin against prostate cancer cells - Mahima Verma; Shireen Fatima; Asad Syed; Abdallah M. Elgorban; Islem Abid; Ling Shing Wong; Mohd Sajid Khan; Irfan Ahmad Ansari (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Imaging Spectroscopy of Carotenoid Content of Himalayan Broadleaved and Needle-Leaved Canopies from Space - Mahima; Hitendra Padalia; Taibanganba Watham; Ishwari Datt Rai; Subrata Nandy (Journal of the Indian Society of Remote Sensing, 2025)

Biodegradable active nanocomposite-film for modified atmosphere packaging - Neeraj Moun; Sarita Kataria; Abhijith T S; Mahima Chandel; Senthilraja K; Bandana Kumari Sahu; Kamaljit Kaur; VijayaKumar Shanmugam (Journal of Food Engineering, 2025)

Biodistribution Studies of FITC Labelled DP1 and DP1 Encapsulated Coumarin-6 PLGA Nanoparticles in Murine Model - Satvika Sharma; Mahima Chugh; Sheetal Sharma; Mayank Maan; Devinder Kumar Dhawan; Avneet Saini (International Journal of Peptide Research and Therapeutics, 2025)

Spatio-temporal variation of particulate matter (PM10) concerning the COVID-19 pandemic in the major cities of Uttarakhand, India - Amar Deep; Tushar Kandari; Hemwati Nandan; Mahima (Journal of Atmospheric and Solar-Terrestrial Physics, 2025)

Advanced human heat exposure sensing using two cylinder anemometer and radiometer: introducing CARla - Konrad Rykaczewski; Ankit Joshi; Shri H. Viswanathan; Emily Parkerson; Mahima Gupta; Michael Park; Isabella DeClair; Kambiz Sadeghi; Sylwester Wereski; Gokul Pathikonda; Jennifer K. Vanos; Ariane Middel (International Journal of Biometeorology, 2025)

Enhancing soybean growth under drought stress through bio-priming with desert endophyte Priestua endophytica strain RAE-11 - Mahima Choudhary; Bhakti Patel; Margi Patel; Nisha Choudhary; Snehal Bagatharia; Rakesh Kumar Verma; Gulab Singh; Virendra Kumar Yadav; Ashish Patel (Symbiosis, 2025)

Assessment of genetic diversity among the natural population of Aerides multiflorum Roxb. from Kangra Valley using RAPD and ISSR markers - Omika Thakur; Shivani Guleria; Mahima Bansal; Anil Kumar (Genetic Resources and Crop Evolution, 2025)

The prowess of metabolomics in cancer research: current trends, challenges and future perspectives - Khushman Taunk; Saikiran Jajula; Praneeta Pradip Bhavsar; Mahima Choudhari; Sadanand Bhanuse; Anup Tamhankar; Tufan Naiya; Bhargab Kalita; Srikanth Rapole (Molecular and Cellular Biochemistry, 2025)

Influence of extraction method of Carica papaya seeds and Chrysanthemum roseum leaves on the acaricidal property against Rhipicephalus microplus - Ankush Rajshekar Dhabale; Nitin Dadarao Jadhav; Anand Srivastava; Macha Vijay; Sachin Kumar; Anil Kumar Sharma; Jagdish Ganpat Gudewar; Mahima Ramesh Narawade; Suresh Gulabrao Jadhao; Sharad Dyandev Chepte; Gajanan Madhavrao Chigure (International Journal of Tropical Insect Science, 2025)

Investigating the coverage of the Arkansas All-Payer Claims Database for examining health disparities related to persistent poverty areas in colorectal cancer patients - Chenghui Li; Cheng Peng; Peter DelNero; Jonathan Laryea; Daniela Ramirez Aguilar; Güneş Koru; Yong-Moon Mark Park; Mahima Saini; Mario Schootman (Cancer Causes & Control, 2025)

Toxicological consequences of yellowjacket wasp and its larvae entomophagy in Himalayan region of Nepal; case report and review of literature - Aayush Adhikari; Rajesh Sharma; Ishwor Thapaliya; Resona Simkhada; Pratik Baral; Mahima Acharya; Sushil Kumar Yadav; Sishir Poudel; Sunil B.K. (Toxicon, 2024)

Experimental and mathematical investigation of cotransport of clay and microplastics in saturated porous media - Mahima John Horta; N. Seetha (Science of The Total Environment, 2024)

Phytogenic microemulsions: Boosting solubility, bioavailability and safety of insecticidal formulations against insect pests and vectors – A comprehensive review - Mahima Chaudhary; Shivani Sharma; Shweta Gupta; Lalit Mohan (Environmental Nanotechnology, Monitoring & Management, 2024)

Molecular characterization, expression and in-silico analysis of fibrinogen-related protein 1 (frep1) in malaria vector Anopheles stephensi - Mahima Yadav; Nisha Dahiya; Vartika Srivastava; Hitesh Singh; Divya Kataria; Sangeeta Janjoter; Ranjnikant Dixit; Neelam Sehrawat (Molecular Biology Reports, 2024)

Alkalimonas mucilaginosa sp. nov. and Alkalimonas cellulosilytica sp. nov. isolated from alkaline Lonar lake, India - Sonia Thite; Devika Godbole; Mahima Debnath; Agrima Bhatt; Amit Yadav; Tushar Lodha; Neetha Joseph; Kiran Kirdat; Dibyajyoti Boruah; Roohani Sharma; Amaraja Joshi (Antonie van Leeuwenhoek, 2024)

Acute Respiratory Syndrome Mimicking Shipping Sickness in Theileria buffeli Infected Buffalo Calf - Varghese Raina; Y. Ajith; Sasi Adithya; S. Anandu; N. Athira; K. S. Athira; P. Preena; K. Vinodkumar; K. Mathew Manju; C. S. Mahima; Jose Akshaya; B. Bruce Alby; et al. (Acta Parasitologica, 2024)

A review of nanocomposites/hybrids made from biomass-derived carbons for electrochemical capacitors - Madhav P. Chavhan; Mahima Khandelwal; Sandeep Arya; Tapas Das; Aditya Singh; Ouassim Ghodbane (Chemical Engineering Journal, 2024)

PM2.5 exposure estimates for college students and health risk assessment - David Daneesh Massey; Mahima Habil (Air Quality, Atmosphere & Health, 2024)

Sustainable Soil Management for Climate Resilience: Long-Term Management Effects on Soil Carbon Sequestration and Nitrogen Dynamics in a Semi-Arid Tropical Inceptisol of India - Debashis Dutta; Amrit Lal Meena; Chandra Bhanu; PC Ghasal; Jairam Choudhary; Sunil Kumar; RP Mishra; MA Ansari; Raghavendra KJ; AK Prusty; P. C. Jat; Poonam Kashyap; et al. (Journal of Soil Science and Plant Nutrition, 2024)

Circular Economy Integration in the Indian FMCG Supply Chain: Unveiling Strategic Hurdles and Pathways to Sustainable Transformation - Shivam Poddar; Mahima Priya; Moupriya Ghosh; Abhishek Kumar Singh; Shatrudhan Pandey (Circular Economy and Sustainability, 2024)

Identification of mycobacterial Thymidylate kinase inhibitors: a comprehensive pharmacophore, machine learning, molecular docking, and molecular dynamics simulation studies - Rupesh V. Chikhale; Surbhi Pravin Pawar; Mahima Sudhir Kolpe; Omkar Dilip Shinde; Kholood A. Dahlous; Saikh Mohammad; Pritee Chunarkar Patil; Shovonlal Bhowmick (Molecular Diversity, 2024)
Thymidylate kinase (TMK) is a pivotal enzyme in Mycobacterium tuberculosis (Mtb), crucial for phosphorylating thymidine monophosphate (dTMP) to thymidine diphosphate (dTDP), thereby playing a critical role in DNA biosynthesis. Dysregulation or inhibition of TMK activity disrupts DNA replication and cell division, making it an attractive target for anti-tuberculosis drug development. In this study, the statistically validated pharmacophore mode was developed from a set of known TMK inhibitors. Further, the robust pharmacophore was considered for screening the Enamine database. The chemical space was reduced through multiple molecular docking approaches, pharmacokinetics, and absolute binding energy estimation. Two different molecular docking algorithms favor the strong binding affinity of the proposed molecules towards TMK. Machine learning-based absolute binding energy also showed the potentiality of the proposed molecules. The binding interactions analysis exposed the strong binding affinity between the proposed molecules and active site amino residues of TMK. Several statistical parameters from all atoms MD simulation explained the stability between proposed molecules and TMK in the dynamic states. The MM-GBSA approach also found a strong binding affinity for each proposed molecule. Therefore, the proposed molecules might be crucial TMK inhibitors for managing Mtb inhibition subjected to in vitro/in vivo validations.

Changes in soil microbial diversity under present land degradation scenario - Mahima Dixit; Debabrata Ghoshal; Amrit Lal Meena; P.C. Ghasal; Ashutosh Kumar Rai; Jairam Choudhary; Debashis Dutta (Total Environment Advances, 2024)

Prospective applications of chitosan and chitosan-based nanoparticles formulations in sustainable agricultural practices - Bhoomika M. Karamchandani; Sunil G. Dalvi; Mahima Bagayatkar; Ibrahim M. Banat; Surekha K. Satpute (Biocatalysis and Agricultural Biotechnology, 2024)

A simple three-cylinder radiometer and low-speed anemometer to characterize human extreme heat exposure - Konrad Rykaczewski; Ankit Joshi; Shri H. Viswanathan; Sai S. Guddanti; Kambiz Sadeghi; Mahima Gupta; Ankush K. Jaiswal; Krishna Kompally; Gokul Pathikonda; Riley Barlett; Jennifer K. Vanos; Ariane Middel (International Journal of Biometeorology, 2024)

Lipidic Nanosystem as State-of-the-Art Nanovehicle for Biomedical Applications - Shivam Otavi; Niyatiben Lad; Sweety Shah; Aniket Navale; Sweta Acharya; Gagandeep Kaur; Mahima Mishra; Rakesh Kumar Tekade (Indian Journal of Microbiology, 2024)

Recent advances of nanomaterials for non-steroidal anti-inflammatory drugs removal from wastewater: a critical review - Jimmy Mangalam; Jyoti Sharma; Mahima Sharma; Yogendra Kumar Mishra; Subhasha Nigam; Monika Joshi (Clean Technologies and Environmental Policy, 2024)

Multi-perspective Investigations of Aerosol’s Non-linear Impact on Unmanned Aerial Vehicle for Air Pollution Control Applications Under Various Aerosol Working Environments - Gopinath Vinayagam; Ragavendra Thaiyan Rajendran; Mahima Swetha Mohan; Beena Stanislaus Arputharaj; Shyam Sundar Jayakumar; Sundhar Baskar; Parvathy Rajendran; Raj Kumar Gnanasekaran; Senthil Kumar Madasamy; Vijayanandh Raja (Aerosol Science and Engineering, 2024)

Phylogenomic analysis of metagenome-assembled genomes indicates new taxa in the order Spirochaetales and proposal of Thalassospirochaeta sargassi gen. nov. sp. nov. from seaweeds - Kohli Pragya; Pannikurungottu Sreya; Lakshmanan Vighnesh; Dhurka Mahima; Mallick Sushmita; Chintalapati Sasikala; Chintalapati Venkata Ramana (Systematic and Applied Microbiology, 2024)

Assessment of Aboveground Biomass in a Tropical Dry Deciduous Forest Using PRISMA Data - Rajani Kant Verma; Laxmi Kant Sharma; Kariya Ishita Bhaveshkumar; Mahima Kanwar Rathore (Journal of the Indian Society of Remote Sensing, 2024)

Time for sustainable marketing to build a green conscience in consumers: Evidence from a hybrid review - Mahima Yadav; Ruchi Gupta; Kiran Nair (Journal of Cleaner Production, 2024)

Biochemical analysis of H2O2-induced mutation spectra revealed that multiple damages were involved in the mutational process - Tomohiko Sugiyama; Mahima R. Sanyal (DNA Repair, 2024)

Comparative Analysis of Sugarcane Production for South East Asia Region - Supriya; Aditya Bhooshan Srivastava; Binita Kumari; Shikha Yadav; Alok Shrivastava; Mahima Priyanka Neerugatti (Sugar Tech, 2024)

Performance of Sugarcane Bud Chip Settlings Under Different Integrated Nutrient Management Practices - Mahima Begum; Bijnan Chandra Bordoloi; Nayan Jyoti Ojha; Khagen Kurmi; Ranjan Das; Dhiman Dev Singha; Kalyan Pathak (Sugar Tech, 2024)

Packaging waste trends in the age of sustainability: a case study of online shopping behaviour pre and post-COVID - Mahima Kadam; Rewa Bochare (Environment, Development and Sustainability, 2023)

Qualitative and quantitative assessment of diatom deformities and protoplasmic condition under metal and metalloid stress - Sudeeksha Negi; Taejun Han; Jihae Park; Elizabeth A. Bergey; Sangeeta; Jyoti Chaubey; Abhishek Kumar; Divyanshi Gupta; Mahima Gupta; Shivangi Singh; Lalit Kumar Pandey (Protoplasma, 2023)

Circular RNA ciRS-7 signature as a potential biomarker for the early detection of diabetes with Alzheimer’s disease: a hypothesis - Mahima Singh; Ajay Guru; Raghul Murugan; Muthukaruppan Gopi; Jesu Arockiaraj (Molecular Biology Reports, 2023)

Retraction Note: Bacopa monnieri attenuates glutamate-induced nociception and brain mitochondrial toxicity in zebrafish - Mahima Sharma; Pankaj Gupta; Debapriya Garabadu (Metabolic Brain Disease, 2023)

Efficacy of species distribution models (SDMs) for ecological realms to ascertain biological conservation and practices - Mahima Kanwar Rathore; Laxmi Kant Sharma (Biodiversity and Conservation, 2023)

Valorization of banana peel into α-amylase using one factor at a time (OFAT) assisted artificial neural network (ANN) and its partial purification, characterization, and kinetics study - Shyama Prasad Saha; Shubham Ghosh; Deepika Mazumdar; Sarbobhouma Ghosh; Dipanwita Ghosh; Mahima Misti Sarkar; Swarnendu Roy (Food Bioscience, 2023)

Mosquito gene targeted RNAi studies for vector control - Mahima Yadav; Nisha Dahiya; Neelam Sehrawat (Functional & Integrative Genomics, 2023)

Valorisation of fruit peel bioactive into green synthesized silver nanoparticles to modify cellulose wrapper for shelf-life extension of packaged bread - Krishna Gopalakrishnan; Mahima Chandel; Vanshita Gupta; Kuljinder Kaur; Ajay Patel; Kamaljit Kaur; Anand Kishore; Pramod K. Prabhakar; Anurag Singh; Jai Shankar Prasad; Vikrant Bodana; Vikas Saxena; et al. (Food Research International, 2023)

Chloroquine induces transitory attenuation of proliferation of human lung cancer cells through regulation of mutant P53 and YAP - Heena Saini; Mahima Choudhary; Harshita Sharma; Shibasish Chowdhury; Sudeshna Mukherjee; Rajdeep Chowdhury (Molecular Biology Reports, 2023)

Boat paint and epoxy fragments - Leading contributors of microplastic pollution in surface waters of a protected Andaman bay - Mahima Jaini; Naveen Namboothri (Chemosphere, 2023)

Evaluation of change points and persistence of extreme climatic indices across India - M. Soorya Gayathri; S. Adarsh; K. Shehinamol; Zaina Nizamudeen; Mahima R. Lal (Natural Hazards, 2022)

Multi-stage classification of Alzheimer’s disease from 18F-FDG-PET images using deep learning techniques - Mahima Thakur; U. Snekhalatha (Physical and Engineering Sciences in Medicine, 2022)

Design of ECM Functionalized Polycaprolactone Aligned Nanofibers for Peripheral Nerve Tissue Engineering - Manasa Nune; Mahima Bhat; Aishwarya Nagarajan (Journal of Medical and Biological Engineering, 2022)
Purpose Peripheral nerve injury (PNI) and its regeneration continue to remain a significant medical burden worldwide. The current treatment strategies used to treat PNI are often associated with multiple complications and yet do not achieve complete motor and sensory functions. Recently, synthetic biodegradable nerve conduits have become one the most commonly used conduits to repair small gaps in nerve injury. But they have not shown better results than nerve grafts possibly because of the lack of biological microenvironment required for axonal growth. Schwann cells play a very crucial role in peripheral nerve regeneration where activated SCs produce multiple neurotrophic factors that help in remyelination and immune modulation during nerve repair. Studies have shown that nanofibrous scaffolds have better bioactivity and more closely mimic the native structure of the extracellular matrix. Therefore, the present study was focused on designing a nanofibrous scaffold that would cover the roles of both structural support for the cells that can provide a microenvironment with biological cues for nerve growth and regeneration. Methods Decellularized Schwann cell ECM were spin-coated on polycaprolactone random and aligned nanofibrous scaffolds and their compatibility was evaluated using Schwann cells. Results Schwann cells displayed growth in the direction of the aligned PCL nanofibers and ACM treated exhibited appropriate bipolar morphology indicating that these modified fibers could provide directional cues making them highly suitable for neuronal cell growth. Conclusion Our results indicate that the fabricated aligned SC-ACM treated PCL scaffolds would be a potential biomaterial to treat peripheral nerve injuries and promote regeneration. Graphical Abstract

RETRACTED ARTICLE: Bacopa monnieri attenuates glutamate-induced nociception and brain mitochondrial toxicity in Zebrafish - Mahima Sharma; Pankaj Gupta; Debapriya Garabadu (Metabolic Brain Disease, 2022)

Fear of the dark: substrate preference in Amazonian tadpoles - Izabela Sabrina Campos Guimarães; Mahima Hemnani; Igor Luis Kaefer; Tiago Henrique da Silva Pires (acta ethologica, 2021)

Durability and microstructural studies on fly ash blended self-compacting geopolymer concrete - Mahima Ganeshan; Sreevidya Venkataraman (European Journal of Environmental and Civil Engineering, 2021)

Degradation of synthetic dyes using nanoparticles: a mini-review - Malvika Mehta; Mahima Sharma; Kamni Pathania; Pabitra Kumar Jena; Indu Bhushan (Environmental Science and Pollution Research, 2021)

Removal of chromate ions from leachate-contaminated groundwater samples of Khan Chandpur, India, using chitin modified iron-enriched hydroxyapatite nanocomposite - Jai Kishan Rajak; Nitin Khandelwal; Mahima Prasad Behera; Ekta Tiwari; Nisha Singh; Zahid Ahmad Ganie; Gopala Krishna Darbha; Fazel Abdolahpur Monikh; Thorsten Schäfer (Environmental Science and Pollution Research, 2021)

Diversity of Indian Barnacles in Marine Provinces and Ecoregions of the Indian Ocean - Jigneshkumar Trivedi; Krupal Patel; Benny K. K. Chan; Mahima Doshi; Vinay Padate (Frontiers in Marine Science, 2021)
The present study is the first completed and taxonomically validated literature review of the biodiversity of barnacles (Cirripedia) in India. A total of 144 species in 75 genera and 19 families have been recorded in India. The highest number of species has been recorded from the Bay of Bengal province, located on the eastern side of the Indian Peninsula, comprising the Eastern India ecoregion (76 species) and Northern Bay of Bengal ecoregion (34 species). The West and South India Shelf province has fewer species (Western India ecoregion: 29 species; South India and Sri Lanka ecoregion: 40 species; and Maldives ecoregion: 10 species) compared to the Bay of Bengal province. The Andaman province is composed of the Andaman and Nicobar Islands, and contains 65 species. Most of the coral-associated barnacles (family Pyrgomatidae) have been recorded in the corals reefs of the Andaman and Nicobar Islands (7 species), Eastern India (6 species), and Northern Bay of Bengal ecoregions (5 species). Sponge-associated barnacles (mostly in the subfamily Acastinae) were recorded in the Eastern India ecoregion, Southern India and Sri Lanka, and Andaman and Nicobar Islands ecoregions. Deepwater species were recorded the most extensively in the Andaman and Nicobar Islands ecoregion (21 species), followed by the South India and Sri Lanka ecoregion (9 species) and Eastern India ecoregion (7 species). Six Atlantic/boreal cold water species previously reported in India were removed due to incorrect identification, and some incorrectly identified species were validated and corrected.

Innovative application of facile single pot green synthesized CuO and CuO@APTES nanoparticles in nanopriming of Vigna radiata seeds - Niloy Sarkar; Radhey Shyam Sharma; Mahima Kaushik (Environmental Science and Pollution Research, 2021)

Talaromyces pinophilus strain M13: a portrayal of novel groundbreaking fungal strain for phytointensification - Dhavalkumar Patel; Abhishek Patel; Mahima Patel; Dweipayan Goswami (Environmental Science and Pollution Research, 2021)

Assessment of GO/ZnO nanocomposite for solar-assisted photocatalytic degradation of industrial dye and textile effluent - Mahima Sharma; Harpreet Sondhi; Richa Krishna; Sanjeev Kumar Srivastava; Parasmani Rajput; Subhasha Nigam; Monika Joshi (Environmental Science and Pollution Research, 2020)

Liposome-Based Study Provides Insight into Cellular Internalization Mechanism of Mosquito-Larvicidal BinAB Toxin - Mahima Sharma; Amit Kumar; Vinay Kumar (The Journal of Membrane Biology, 2020)

Biochar–nZVI nanocomposite: optimization of grain size and Fe0 loading, application and removal mechanism of anionic metal species from soft water, hard water and groundwater - Nitin Khandelwal; Mahima Prasad Behera; Jai Kishan Rajak; Gopala Krishna Darbha (Clean Technologies and Environmental Policy, 2020)

Eugenol Attenuates Scopolamine-Induced Hippocampal Cholinergic, Glutamatergic, and Mitochondrial Toxicity in Experimental Rats - Debapriya Garabadu; Mahima Sharma (Neurotoxicity Research, 2019)

A topological transition from bimolecular quadruplex to G-triplex/tri-G-quadruplex exhibited by truncated double repeats of human telomere - Mohan Kumar; Mahima Kaushik; Shrikant Kukreti (European Biophysics Journal, 2018)

Molecular analysis of influenza A H1N1pdm09 virus circulating in Madhya Pradesh, India in the year 2017 - Salonee Pandey; Mahima Sahu; Varsha Potdar; Pradip Barde (VirusDisease, 2018)

Comparing human peritoneal fluid and phosphate-buffered saline for drug delivery: do we need bio-relevant media? - Prabhat Bhusal; Jamie Lee Rahiri; Bruce Sua; Jessica E. McDonald; Mahima Bansal; Sara Hanning; Manisha Sharma; Kaushik Chandramouli; Jeff Harrison; Georgina Procter; Gavin Andrews; David S. Jones; et al. (Drug Delivery and Translational Research, 2018)

Th2-biased immune response and agglutinating antibodies generation by a chimeric protein comprising OmpC epitope (323–336) of Aeromonas hydrophila and LTB - Mahima Sharma; Pujarini Dash; Pramod K. Sahoo; Aparna Dixit (Immunologic Research, 2018)

Optimization of cell growth and bacoside-A production in suspension cultures of Bacopa monnieri (L.) Wettst. using response surface methodology - Mahima Bansal; M. Sudhakara Reddy; Anil Kumar (In Vitro Cellular & Developmental Biology - Plant, 2017)

Bdnf mRNA splice variants differentially impact CA1 and CA3 dendrite complexity and spine morphology in the hippocampus - Kristen R. Maynard; John W. Hobbs; Mahima Sukumar; Alisha S. Kardian; Dennisse V. Jimenez; Robert J. Schloesser; Keri Martinowich (Brain Structure and Function, 2017)

Recombinant outer membrane protein C of Aeromonas hydrophila elicits mixed immune response and generates agglutinating antibodies - Sunita Kumari Yadav; Jitendra Kumar Meena; Mahima Sharma; Aparna Dixit (Immunologic Research, 2016)

Crystal structure analysis of C-phycoerythrin from marine cyanobacterium Phormidium sp. A09DM - Vinay Kumar; Ravi R. Sonani; Mahima Sharma; Gagan D. Gupta; Datta Madamwar (Photosynthesis Research, 2016)

Seasonal variations in harvest index and bacoside A contents amongst accessions of Bacopa monnieri (L.) Wettst. collected from wild populations - Mahima Bansal; M. Sudhakara Reddy; Anil Kumar (Physiology and Molecular Biology of Plants, 2016)

Influence of Agrobacterium rhizogenes strains on hairy root induction and ‘bacoside A’ production from Bacopa monnieri (L.) Wettst. - Mahima Bansal; Anil Kumar; M. Sudhakara Reddy (Acta Physiologiae Plantarum, 2014)

Evidence for vital role of endo-β-N-acetylglucosaminidase in the resistance of Arthrobacter protophormiae RKJ100 towards elevated concentrations of o-nitrobenzoate - Janmejay Pandey; Fazlurrahman Khan; Vivek Mahajan; Mahima Pant; Rakesh K. Jain; Gunjan Pandey (Extremophiles, 2014)

Diversity among wild accessions of Bacopa monnieri (L.) Wettst. and their morphogenetic potential - Mahima Bansal; Anil Kumar; M. Sudhakara Reddy (Acta Physiologiae Plantarum, 2014)

Exposure of children studying in schools of India to PM levels and metal contamination: sources and their identification - Mahima Habil; David D. Massey; Ajay Taneja (Air Quality, Atmosphere & Health, 2013)

MTHFR C677T Polymorphism Among Three Mendelian Populations: A Study from North India - Seerat Sachdeva; Kallur N. Saraswathy; Mahima Gulabani; Shweta Kaushik; M. P. Sachdeva; Manju Puri; S. L. Malik (Biochemical Genetics, 2012)

Ligand-based drug design studies using predictive pharmacophore model generation on 4H-1,2,4-triazoles as AT1 receptor antagonists - Sarvesh Paliwal; Mahima Pal; Divya Yadav; Supriya Singh; Rakesh Yadav (Medicinal Chemistry Research, 2012)

In Vivo MicroRNA Detection and Quantitation in Cerebrospinal Fluid - Juan A. Gallego; Marc L. Gordon; Kierstyn Claycomb; Mahima Bhatt; Todd Lencz; Anil K. Malhotra (Journal of Molecular Neuroscience, 2012)

BMP depletion occurs during prolonged acid demineralization of bone: characterization and implications for graft preparation - William S. Pietrzak; Saba N. Ali; Deepika Chitturi; Mahima Jacob; Jennifer E. Woodell-May (Cell and Tissue Banking, 2011)

Quantitative structure activity relationship analysis of angiotensin II AT1 receptor antagonists - Sarvesh Kumar Paliwal; Mahima Pal; Anees A. Siddiqui (Medicinal Chemistry Research, 2010)

Enzymatic properties of the ferredoxin-dependent nitrite reductase from Chlamydomonas reinhardtii. Evidence for hydroxylamine as a late intermediate in ammonia production - Masakazu Hirasawa; Jatindra N. Tripathy; Frederik Sommer; Ramasamy Somasundaram; Jung-Sung Chung; Matthew Nestander; Mahima Kruthiventi; Masoud Zabet-Moghaddam; Michael K. Johnson; Sabeeha S. Merchant; James P. Allen; David B. Knaff (Photosynthesis Research, 2010)

Effect of Organic Selenium Supplementation on Growth, Se Uptake, and Nutrient Utilization in Guinea Pigs - Mahima Chaudhary; Anil Kumar Garg; Ganesh Kumar Mittal; Vishal Mudgal (Biological Trace Element Research, 2010)